MODEL REDUKSI PADA PARAMETER MARKOV - Farikhin, Farikhin (MATEMATIKA, 2011)
As well known that the model reduction for large-scale linear dynamical systems based on Krylov subspace is called moments matching. In this method, one or more interpolation points is needed to constructÂ a certain Krylov subspace. In this paper, we propose the proof of theorem for moment matching at Markov parameter using the theorem which is obtained from standard block Arnoldi algorithm.